Redesigh Gravitation Water Vortex Power Plant (GWVPP) Study Kasus Desa Duren - Basri, Muhammad Hasan; Pratama, Bayu Okta; Faisol, Muhammad; Abidin, Ali Zainal; Billah, Moh Arif (Universitas Nurul Jadid, 2021)
Residents in remote areas have not been able to enjoy electricity, including Desa Duren, Gading District, located in the mountainous area south of Probolinggo Regency, where the village still does not receive electricity supply from PLN. Hydropower is a renewable energy that can be used as a substitute for generators, where this potential can be used to become a Gravitation Water Vortex Power Plant (GWVPP) already in the village, but it needs a touch of redesign. The results of the research on the reduction of gravitation water vortex power pland in Duren Village can be obtained that the electric power generated is 727.7 watts, where this power can supply electricity needs of 5 houses.